Pengaruh Bauran Pemasaran Jasa Pada Kepuasan Pelanggan JNE - Alven, Alven; Marcelino, Samuel Indra; Khasanah, Iiswatun (Jurnal Ilmiah Wahana Pendidikan, 2025)
The development of service marketing today plays an important and rapidly growing role in terms of distribution (delivery or forwarding) both in terms of distribution of goods and services to consumers in a country. The services provided by the company have the benefit of providing to consumers. Standard operating procedures are important for companies to follow to recognise customer satisfaction and company performance satisfaction. In addition, it prevents consumers from switching to other service companies. This study uses a quantitative approach by distributing questionnaires. The analysis method used is to use SPSS 23 software. The results showed that the Service Marketing Mix had a positive effect on Customer Satisfaction. This shows that JNE needs to improve its services so that users continue to use JNE on an ongoing basis.